Whole-Genome Methylation Analysis Reveals Epigenetic Variation in Cloned and Donor Pigs - Wang, Mengfen; Feng, Shuaifei; Ma, Guanjun; Miao, Yiliang; Zuo, Bo; Ruan, Jinxue; Zhao, Shuhong; Wang, Haiyan; Du, Xiaoyong; Liu, Xiangdong (Frontiers in Genetics, 2020)
Somatic cloning has played important roles in animal production, basic science and human medical research. However, the epigenetic variation between cloned and donor animals is unclear, and low efficiency limits the application of somatic cloning. DNA methylation is a common epigenetic pattern in mammals and an important factor of phenotype in animals. To explore the cloning effect on the epigenetic inheritance and phenotype of cloned animals, we selected the blood and ear of one cloned pig and one donor pig to perform a whole-genome bisulphite sequencing to reveal the epigenetic modifications in cloning. A total of 216 and 707 differential methylation genes (DMGs) were identified in the blood and ear, respectively. The functional annotation showed that DMGs were enriched in many pathways, including T/B or NK cell differentiation, oocyte maturation, embryonic development and reproductive hormone secretion. Moreover, 22 and 75 DMGs in the blood and ear, respectively, were associated with immunity. The important immune regulatory factors, namely, CD244, CDK6, CD5, CD2, CD83 and CDC7, were differentially methylated between the cloned and donor pigs, possibly leading to immune differences of these two pigs. Meanwhile, 18 and 53 DMGs in the blood and ear, respectively, and the important genes, namely, ITPR2, TAPT1, GNAS and EGFR, were related to reproduction. Such genes were differentially methylated in the two pigs, possibly leading to low fertility of the cloned pig. Epigenetic variation existed between the cloned pig and the donor pig. Additionally, the genes related to immunity and reproduction differed in methylation between these two pigs, but they did not necessarily result in a significant phenotypic abnormality of cloned animals. However, the phenotypic variation caused by cloning had few effects on animal production, suggesting an effective way of achieving high-yielding animal production.